Polishing composition
Patent Information
- Application Number
- CN202180010578.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-20
- Filing Date
- 2021-01-22
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-01-22
AI Technical Summary
After the existing grinding compositions are polished with semiconductor substrates, they often increase the surface slight defects and roughness, making it difficult to achieve high-grade surface effects.
Using a grinding composition containing specific water-soluble polymers, specifically a vinyl alcohol resin, optimizes the grinding process to reduce LLS defects and AFM roughness by adjusting its side chain groups and saponification degree, combining abrasive particles and surfactants. .
It effectively reduces the tiny defects and haze on the surface after grinding, improves the optical taste and mechanical optical properties of the surface, and is suitable for the manufacturing of semiconductor devices.
Smart Images

Figure BDA0003759246470000081 
Figure BDA0003759246470000401 
Figure BDA0003759246470000411
Abstract
Description
Technical Field
[0001] The present invention relates to a novel polishing composition, etc. Background Art
[0002] The surface of a silicon wafer used as a component of a semiconductor device is usually processed into a high-quality mirror surface through a lapping process (rough lapping process, lapping) and a polishing process (precision lapping process, polishing). As a typical example, the polishing process includes a primary polishing process (primary lapping process) and a final polishing process (final lapping process).
[0003] In the above-mentioned polishing step, a polishing composition is used.
[0004] As polishing compositions, those containing a water-soluble polymer are known. For example, Patent Document 1 describes a polishing composition containing hydroxyethyl cellulose and / or polyvinyl alcohol and a block polyether.
[0005] Furthermore, Patent Document 2 discloses a semiconductor wetting agent containing a water-soluble polymer (such as hydroxyethyl cellulose, polyvinyl alcohol, and polyvinyl pyrrolidone) having a specific viscosity.
[0006] Furthermore, in recent years, semiconductor substrates such as silicon wafers and other substrates are being required to have surfaces of higher quality.
[0007] Specifically, it is required to reduce microscopic surface defects (for example, surface defects called LPD (Light Point Defect)) and roughness, etc. It is known that surface defects can be detected by light scattering as LLS (Localized Light Scatters) defects.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2005-85858
[0011] Patent Document 2: Japanese Patent Application Publication No. 2010-34509 Summary of the invention
[0012] Technical Problems to be Solved by the Invention
[0013] The object of the present invention is to provide a novel polishing composition.
[0014] Another object of the present invention is to provide a polishing composition that can reduce the number of micro defects on a surface after polishing (particularly polishing of a semiconductor substrate such as a silicon wafer).
[0015] Another object of the present invention is to provide a polishing composition having a small haze on the surface after polishing.
[0016] Furthermore, another object of the present invention is to provide a polishing composition having a small AFM roughness (roughness measured by AFM) of the polished surface.
[0017] Another object of the present invention is to provide a method for producing a polished article using the polishing composition.
[0018] Technical means to solve technical problems
[0019] The inventors of the present application focused on defects of smaller size than before on the surface of a substrate such as a semiconductor substrate after grinding, and found that when the surface of a semiconductor substrate is ground using a grinding composition containing a water-soluble polymer, the number of tiny defects on the surface of the semiconductor substrate after grinding sometimes increases depending on the type of the water-soluble polymer.
[0020] In order to solve the above-mentioned technical problems, the inventors of the present application have repeatedly conducted in-depth research and found that by using a polishing composition containing specific water-soluble polymers, the number of tiny defects (especially LLS defects larger than 26 nm or larger than 19 nm) on the surface of the semiconductor substrate after polishing can be reduced.
[0021] The inventors of the present application have also found that the use of the polishing composition described above can reduce the haze or AFM roughness of the surface of the semiconductor substrate after polishing.
[0022] That is, the present invention relates to the following inventions and the like.
[0023] (1) A polishing composition comprising a water-soluble polymer, wherein the water-soluble polymer contains at least a vinyl alcohol-based resin (A) having a side chain group having 3 or more carbon atoms.
[0024] (2) A polishing composition comprising a water-soluble polymer, wherein the water-soluble polymer comprises at least a vinyl alcohol resin (B), wherein the vinyl alcohol resin (B) is at least one selected from a vinyl alcohol resin (B1) having a saponification degree greater than 90 mol % and a 4% aqueous solution viscosity of 300 mPa·s or less at 20°C, and a vinyl alcohol resin (B2) having a saponification degree of 90 mol % or less.
[0025] (3) The polishing composition according to (1), wherein the side chain group comprises a 7-30 Fatty acid-vinyl ester radical, from C 3-30 At least one of an alkyl vinyl ether group, a group derived from an aromatic carboxylic acid vinyl ester, a group derived from diacetone (meth) acrylamide, and an epoxy ring-opened product of a group derived from a vinyl monomer containing an acetoacetyl group and an epoxy group.
[0026] (4) The polishing composition according to (1), wherein the side chain group comprises at least one selected from a group derived from a fatty acid-vinyl ester having 3 or more carbon atoms, a group derived from an aromatic carboxylic acid vinyl ester, a group derived from diacetone (meth)acrylamide, and a polyoxyethylene group.
[0027] (5) The polishing composition according to any one of (1) to (3), wherein the side chain group comprises a 3-30 At least one of a group of an alkyl vinyl ether and a group derived from diacetone (meth)acrylamide.
[0028] (6) The polishing composition according to any one of (1) and (3) to (5), wherein the side chain group contains at least a group derived from diacetone (meth)acrylamide.
[0029] (7) A polishing composition according to (1), wherein the side chain group having 3 or more carbon atoms of the vinyl alcohol resin (A) contains a group derived from an alkyl vinyl ether having 4 or more carbon atoms, and the vinyl alcohol resin (A) has a 4% aqueous solution viscosity of 100 mPa·s or more at 20°C and a number average molecular weight of 10,000 or more.
[0030] (8) The polishing composition according to any one of (1) and (3) to (7), wherein the ratio of the side chain group is 0.05 mol % or more in terms of the polymerized component (monomer).
[0031] (9) The polishing composition according to (2), wherein the water-soluble polymer contains a vinyl alcohol resin (B1).
[0032] (10) The polishing composition according to (2), wherein the vinyl alcohol resin (B) consists essentially of only vinyl alcohol units and vinyl ester units.
[0033] (11) The polishing composition according to any one of (1) and (3) to (8), wherein the vinyl alcohol resin (A) has a saponification degree of 80 to 99.9 mol % and a viscosity of a 4% aqueous solution at 20°C of 1 to 300 mPa·s.
[0034] (12) The polishing composition according to any one of (1) to (11), further comprising abrasive grains.
[0035] (13) The polishing composition according to any one of (1) to (12), further comprising a pH adjuster.
[0036] (14) The polishing composition according to any one of (1) to (13), further comprising abrasive grains and a pH adjuster, wherein the abrasive grains contain silica and the pH adjuster contains a basic compound.
[0037] (15) The polishing composition according to (2), wherein the water-soluble polymer contains a vinyl alcohol resin (B2), and the abrasive particles contain silica.
[0038] (16) The polishing composition according to any one of (1) to (15), further comprising a surfactant.
[0039] (17) The polishing composition according to any one of (1) to (16), further comprising a surfactant, wherein the surfactant comprises at least one selected from a copolymer having an oxyethylene-oxypropylene structure and a polyoxyethylene alkyl ether.
[0040] (18) The polishing composition according to any one of (1) to (17), further comprising a surfactant, wherein the ratio of the water-soluble polymer to the surfactant is 1:0.01 to 1:200 by mass.
[0041] (19) The polishing composition according to any one of (1) to (18), further comprising a solvent containing at least water, wherein the concentration of the water-soluble polymer is 1 ppm or more.
[0042] (20) The polishing composition according to any one of (1) to (19), further comprising a solvent containing at least water, wherein the polishing composition has a solid content concentration of 0.01 mass % or more.
[0043] (21) A polishing composition comprising a water-soluble polymer, wherein the polished surface of an object to be polished after polishing and washing satisfies the following condition (A):
[0044] (A) The number of LLS defects of 26 nm or more is 700 or less per 300 mm diameter.
[0045] (22) A polishing composition comprising a water-soluble polymer, wherein the polished surface of an object to be polished after polishing and washing satisfies the following condition (B):
[0046] (B) The number of LLS defects larger than 19 nm is 850 or less per 300 mm diameter.
[0047] (23) A method for producing a polished object, comprising the step of polishing a surface of an object to be polished using the polishing composition according to any one of (1) to (22).
[0048] (24) The method for producing a polished product according to (23), comprising a dilution step of diluting the polishing composition using a solvent containing at least water, and in the polishing step, polishing is performed using the diluted solution obtained in the dilution step.
[0049] (25) The method for producing a polished article according to (23) or (24), wherein the polished article has a surface satisfying the following condition (A):
[0050] (A) The number of LLS defects of 26 nm or more is 700 or less per 300 mm diameter.
[0051] (26) A grinding material, the surface of which satisfies the following condition (A):
[0052] (A) The number of LLS defects of 26 nm or more is 700 or less per 300 mm diameter.
[0053] (27) A method for reducing the number of LLS defects on a polished surface, comprising the step of polishing the surface of an object to be polished using the polishing composition according to any one of (1) to (22).
[0054] Effects of the Invention
[0055] According to the present invention, a novel polishing composition can be provided.
[0056] According to the above composition, since the number of tiny defects (especially LLS defects larger than 26nm or larger than 19nm) on the surface after grinding (especially grinding of semiconductor substrates such as silicon wafers) can be reduced, a grind having a high-quality surface can be obtained.
[0057] Furthermore, according to the above composition, since the haze of the surface after the polishing can be reduced, a polished product having a high-quality surface can be obtained.
[0058] Furthermore, according to the above composition, since the AFM roughness (particularly the roughness at a long wavelength) of the polished surface can be reduced, effective focusing can be achieved during exposure in manufacturing a semiconductor device.
[0059] Furthermore, according to the above composition, a semiconductor device or the like can be efficiently formed.
[0060] Furthermore, the present invention can provide a method for producing a polished product using the above-mentioned composition. DETAILED DESCRIPTION
[0061] (Composition)
[0062] The composition of the present invention usually contains a specific water-soluble polymer described below. The composition of the present invention can be used particularly for polishing.
[0063] (Water-soluble polymer)
[0064] In the composition, the water-soluble polymer may contain a vinyl alcohol-based resin (A) having a side chain group having 3 or more carbon atoms.
[0065] (Vinyl alcohol resin (A))
[0066] The vinyl alcohol-based resin is generally a polyvinyl alcohol-based resin (sometimes also referred to as a PVA-based resin, PVA, etc.), which is a saponified product of a vinyl ester-based polymer (a polymer containing at least a vinyl ester as a polymerization component).
[0067] The vinyl ester (vinyl ester monomer) is not particularly limited, and examples thereof include vinyl esters of fatty acids [e.g., vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl octanoate, vinyl neodecanoate, vinyl monochloroacetate, etc. 1-30 Fatty acid-vinyl esters (e.g. C 1-16 Alkane acid-vinyl esters) etc.], aromatic carboxylic acid vinyl esters [such as benzoic acid vinyl esters and other aromatic carboxylic acid vinyl esters (such as C 7-12 Aromatic carboxylic acid-vinyl ester) etc.]
[0068] The vinyl esters may be used alone or in combination of two or more.
[0069] The vinyl ester preferably contains at least a fatty acid vinyl ester (e.g., vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, etc.) 1-10 Alkane acid-vinyl esters, etc.), and from an industrial point of view, in particular, vinyl acetate may be contained.
[0070] The vinyl ester polymer may have a unit derived from other monomers (monomers copolymerizable with vinyl ester) as necessary (may be modified by other monomers).
[0071] Other monomers are not particularly limited, for example, alkyl vinyl ethers (such as hexadecyl vinyl ether, etc.) 1-30 Alkyl vinyl ether, preferably C 1-16 alkyl vinyl ethers), epoxy-containing vinyl monomers {e.g., vinyl glycidyl ethers (e.g., allyl glycidyl ether, (meth) acrylic acid glycidyl ether, 4-(meth) acrylamide phenyl glycidyl ether, 3-(meth) acrylamide phenyl glycidyl ether, N-glycidoxymethyl (meth) acrylamide, N-glycidoxyethyl (meth) acrylamide, N-glycidoxypropyl (meth) acrylamide, N-glycidoxybutyl (meth) acrylamide, 4-(meth) acrylamide methyl-2- ,5-dimethyl-phenyl glycidyl ether), epoxy-containing α-olefins (e.g. 1,2-epoxy-5-hexene, 1,2-epoxy-7-octene, 1,2-epoxy-9-decene, 8-hydroxy-6,7-epoxy-1-octene, 8-acetoxy-6,7-epoxy-1-octene), N-(2,3-epoxy)propyl(meth)acrylamide, (meth)acrylamidepropyldimethyl(2,3-epoxy)propylammonium chloride, (meth)acrylate glycidyl, etc.), α-olefins ( (e.g. ethylene, propylene, etc.), (meth)acrylates [e.g. methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate and other (meth)acrylate alkyl esters, diacetone (meth)acrylate], unsaturated amides [e.g. (meth)acrylamide, diacetone (meth)acrylamide, N-methylol acrylamide, etc.], unsaturated acids {e.g. unsaturated acids [e.g. (meth)acrylic acid, crotonic acid, maleic acid, itaconic acid, fumaric acid, etc.], unsaturated acid esters [esters of unsaturated acids other than (meth)acrylic acid, such as alkyl (methyl, ethyl, propyl, etc.) esters, etc.], unsaturated acid anhydrides (maleic anhydride, etc.), salts of unsaturated acids [such as alkali metal salts (such as sodium salts, potassium salts, etc.), ammonium salts, etc.], glycidyl group-containing monomers [such as allyl glycidyl ether, glycidyl (meth)acrylate, etc.], sulfonic acid group-containing monomers (such as 2-acrylamide-2-methylpropanesulfonic acid, salts thereof, etc.), phosphoric acid group-containing monomers [such as acid phosphoxyethyl (meth)acrylate, acid phosphoxypropyl (meth)acrylate, etc.], allyl alcohol, diacetone (meth)acrylamide, etc., but are not particularly limited to these monomers.
[0072] The other monomers may be used alone or in combination of two or more.
[0073] The units derived from vinyl ester or units derived from other monomers may be modified within a range that does not inhibit the effects of the present invention.
[0074] Examples of the modification of the vinyl ester-derived unit include acetalization, etherification, acetoacetylation, cationization, and polyoxyalkylene modification.
[0075] Examples of modification of units derived from other monomers include a ring-opening reaction of an epoxy group (eg, a reaction between an epoxy group and a thiol).
[0076] The modification method is not particularly limited, and examples of the method for acetoacetylation of the unit derived from the vinyl ester include a method of reacting a vinyl alcohol-based resin with diketene.
[0077] The method for reacting the vinyl alcohol resin with diketene is not particularly limited, and examples thereof include the following methods: a method of directly reacting the vinyl alcohol resin with gaseous or liquid diketene; a method of allowing an organic acid to be adsorbed on the vinyl alcohol resin in advance and then spraying gaseous or liquid diketene in an inert gas atmosphere to react; a method of spraying a mixture of an organic acid and liquid diketene onto the vinyl alcohol resin to react.
[0078] Examples of the ring-opening reaction of the epoxy group in the unit derived from another monomer include a method of reacting a unit derived from an epoxy group-containing vinyl monomer with a thiol (for example, a thiol having an amino group).
[0079] The vinyl alcohol-based resin (A) may have at least a side chain group having 3 or more carbon atoms [eg, 3 to 30, 4 to 30, 5 to 30, 6 to 30, 7 or more (eg, 7 to 30)].
[0080] The side chain group having 3 or more carbon atoms may have one or more heteroatoms (e.g., nitrogen atom, oxygen atom, sulfur atom, etc.) In addition, in the side chain group having 3 or more carbon atoms, the heteroatom may be present between carbon atoms.
[0081] Furthermore, the side chain group having 3 or more carbon atoms may have a substituent (eg, an amino group, etc.).
[0082] The vinyl alcohol-based resin (A) may contain one or two or more side chain groups having 3 or more carbon atoms.
[0083] The side chain group having 3 or more carbon atoms may be contained in a monomer serving as a polymerization component of the vinyl ester polymer (i.e., may be a group derived from a monomer of the vinyl ester polymer), or may be introduced by modifying a portion of the vinyl ester polymer or a saponified product of the vinyl ester polymer.
[0084] Examples of the side chain group having 3 or more carbon atoms include an alkyl group (e.g., 3-30 Alkyl, preferably C 3-20Alkyl, more preferably C 6-20 Alkyl), aryl (e.g. C 6-30 Aryl, preferably C 6-20 Aryl, more preferably C 11-20 aryl group), a group represented by the following formula (1), a polyoxyalkylene group (for example, a polyoxyethylene group, a polyoxypropylene group, etc.) 2-6 olefin group), a group having an acetoacetyl group, etc., an epoxy ring-opening product of a group derived from an epoxy-containing vinyl monomer (for example, the epoxy-containing vinyl monomers exemplified above), and the like.
[0085] [Chemical formula 1]
[0086]
[0087] These groups may be directly bonded to the main chain of the vinyl alcohol resin (A) or may be bonded to the main chain via a linking group (for example, an ether bond, an ester bond, an amide bond, a urethane bond, etc.).
[0088] Specific examples of the group having an alkyl group include: 3-30 Fatty acid-vinyl esters (e.g. vinyl propionate, vinyl butyrate, vinyl octanoate, vinyl neodecanoate, etc.) 3-30 Alkane acid-vinyl ester, preferably C 7-30 Alkane acid-vinyl ester, more preferably C 7-20 Alkane acid-vinyl ester) group, from C 3-30 Alkyl vinyl ether [such as hexadecyl vinyl ether, etc. 7-30 Alkyl vinyl ether, preferably C 7-20 Alkyl vinyl ether (such as C 11-20 Alkyl vinyl ether, C 13-20 alkyl vinyl ether, etc.)], having C 3-30 Alkyl (e.g. C 7-30 Alkyl, C 11-30 alkyl group, etc.) and urethane alkyl group.
[0089] Specific examples of the group having an aryl group include groups derived from aromatic carboxylic acid vinyl esters [e.g., aromatic hydrocarbon carboxylic acid vinyl esters such as vinyl benzoate (e.g., C 7-12 Aromatic carboxylic acid-vinyl ester)] group, etc.
[0090] Specific examples of the group having a group represented by the above formula (1) include a group derived from diacetone (meth)acrylamide and a group derived from diacetone (meth)acrylate.
[0091] Examples of epoxy ring-opened products of groups derived from epoxy-group-containing vinyl monomers include those obtained by ring-opening an epoxy group (eg, reaction between an epoxy group and a thiol) on groups derived from epoxy-group-containing vinyl monomers.
[0092] The method for the ring-opening reaction of the epoxy group is not particularly limited, and examples thereof include a method of reacting a unit derived from an epoxy-containing vinyl monomer with a thiol [e.g., a thiol having an amino group (thiol described in Japanese Patent No. 3647630, etc.)] (e.g., the method described in Japanese Patent No. 3647630, etc.).
[0093] The side chain group having 3 or more carbon atoms may be, in particular, 7-30 Fatty acid-vinyl ester radical, from C 3-30 Alkyl vinyl ether group, aromatic carboxylic acid vinyl ester derived group, diacetone (meth) acrylamide derived group, acetoacetyl group, epoxy ring-opened product of the group derived from epoxy group-containing vinyl monomer, etc.
[0094] The vinyl alcohol-based resin (A) can be used alone or in combination of two or more.
[0095] Moreover, as the vinyl alcohol-based resin (A), a commercially available product can be used.
[0096] The method for preparing the vinyl alcohol-based resin (A) is not particularly limited, and for example, a known method such as a method of saponifying a vinyl ester-based polymer can be used.
[0097] The polymerization method of the vinyl ester polymer is not particularly limited, and examples thereof include known bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization. Industrially, solution polymerization (eg, solution polymerization using methanol as a solvent) is preferred.
[0098] In the solution polymerization, a known initiator such as a peroxide-based initiator or an azo-based initiator can be used, and the polymerization degree of the obtained vinyl ester-based polymer can be adjusted by changing the blending ratio of the vinyl ester-based monomer and the solvent and the polymerization yield.
[0099] As a method for saponifying the vinyl ester polymer, a conventionally known saponification method using an alkali catalyst or an acid catalyst can be used. Among them, the following method is industrially preferred: a method in which a base such as sodium hydroxide is added to a methanol solution of the vinyl ester polymer or a mixed solution of methanol, water, methyl acetate, etc. of the vinyl ester polymer, and alcoholysis is performed while stirring and mixing.
[0100] Then, the obtained block-like object, gel-like object or granular object is crushed, and after the added alkali is neutralized as needed, the solid component and the liquid component are separated, and the solid component is dried to obtain the PVA-based resin.
[0101] When modification is performed, the timing of modification is not particularly limited, and the modification may be performed before or after saponification of the vinyl ester polymer.
[0102] Representative examples of the vinyl alcohol resin (A) include saponified products of vinyl ester polymers containing at least vinyl ester and diacetone (meth)acrylamide as polymerization components, saponified products of vinyl ester polymers containing at least vinyl ester having 3 or more carbon atoms in a side chain group as polymerization components, and saponified products of vinyl ester polymers modified with polyoxyalkylene (such as polyoxyethylene groups). Among them, saponified products of vinyl ester polymers containing at least vinyl ester and diacetone (meth)acrylamide as polymerization components are preferred.
[0103] From the perspective of reducing minor defects, etc., in the vinyl alcohol resin (A), the proportion of side chain groups having 3 or more carbon atoms, calculated on the basis of the polymerization components (monomers), may be, for example, 0.05 mol% or more, preferably 0.1 mol% or more, more preferably 0.2 mol% or more, and particularly preferably 0.5 mol% or more.
[0104] In addition, from the perspective of polishing speed, etc., in the vinyl alcohol resin (A), the proportion of side chain groups having 3 or more carbon atoms, calculated as the polymerization component (monomer), can be, for example, 50 mol% or less (for example, 40 mol% or less, 30 mol% or less, 20 mol% or less, 15 mol% or less, 10 mol% or less, etc.).
[0105] In addition, the above upper limit value and lower limit value can be appropriately combined to set an appropriate range (for example, 0.05 to 50 mol %, 0.05 to 40 mol %, etc.) (the same applies to other numerical values).
[0106] Specifically, in the vinyl alcohol resin (A), the proportion of side chain groups having 3 or more carbon atoms, calculated on the basis of the polymerization component (monomer), may be, for example, 0.05 to 20 mol%, preferably 0.1 to 20 mol%, more preferably 0.2 to 20 mol%, and particularly preferably 0.2 to 15 mol% (e.g. 1 to 10 mol%, 3 to 6 mol%).
[0107] In particular, when the vinyl alcohol resin (A) contains a group derived from diacetone (meth) acrylamide, from the viewpoint of improving haze, etc., the ratio of the group derived from diacetone (meth) acrylamide in the vinyl alcohol resin (A) may be, for example, 0.05 to 50 mol%, and preferably 0.2 to 20 mol% (e.g., 0.2 to 15 mol%, 1 to 10 mol%, 3 to 6 mol%), calculated as the polymerized component (monomer).
[0108] The saponification degree of the vinyl alcohol resin (A) is not particularly limited, and may be, for example, 60 mol% or more (e.g., 70 mol% or more), preferably 80 mol% or more (e.g., 81 mol% or more, 82 mol% or more, 83 mol% or more, 84 mol% or more, 85 mol% or more), and more preferably 90 mol% or more (e.g., 91 mol% or more, 92 mol% or more, 93 mol% or more, 94 mol% or more, 95 mol% or more, 96 mol% or more, 97 mol% or more, 98 mol% or more, etc.).
[0109] Although a higher saponification degree of vinyl alcohol resin is preferred from the perspective of water solubility (solubility in polishing liquid), according to the research of the inventors of the present application, when the saponification degree is too high, sometimes the micro defects on the surface of the silicon wafer tend to increase after the surface polishing. However, in the present invention, by using a vinyl alcohol resin (A) having a side chain group with 3 or more carbon atoms, it is easy to reduce the micro defects on the surface of the wafer even when the saponification degree of the vinyl alcohol resin is high.
[0110] The upper limit of the saponification degree of the vinyl alcohol resin (A) is not particularly limited, and may be, for example, 99.9 mol% or less, 99.5 mol% or less, or 99 mol% or less.
[0111] In addition, for the saponification degree of the vinyl alcohol resin (A), the above-mentioned upper limit value and lower limit value can be appropriately combined to set an appropriate range (for example, 80 to 99.9 mol%, 85 to 99 mol%, 90 to 99 mol%, etc.) (the same applies to other numerical values), including all combinations of the above-mentioned upper limit value and lower limit value.
[0112] The saponification degree of the vinyl alcohol-based resin (A) can be measured, for example, by the saponification degree measuring method of JIS K6726.
[0113] The average degree of polymerization of the vinyl alcohol resin (A) is not particularly limited, and may be, for example, 100 to 4000, preferably 200 to 3000, more preferably 300 to 2000, and particularly preferably 500 to 1000.
[0114] According to the research of the inventor of the present application, although vinyl alcohol resins with a higher average degree of polymerization are preferred from the perspectives of improving the protectiveness of the wafer surface and reducing damage to the wafer, if vinyl alcohol resins with a higher average degree of polymerization are used for surface grinding of silicon wafers, there is a tendency that the micro defects on the wafer surface are easily increased. However, in the present invention, by using a vinyl alcohol resin (A) having a side chain group with a carbon number of 3 or more, it is easy to reduce the micro defects on the wafer surface even when the average degree of polymerization of the vinyl alcohol resin is higher.
[0115] The average degree of polymerization of the vinyl alcohol-based resin (A) can be measured, for example, by the method specified in JIS K6726.
[0116] The viscosity of a 4% aqueous solution of the vinyl alcohol resin (A) at 20°C is not particularly limited, and may be, for example, 300 mPa·s or less (e.g. 250 mPa·s or less), preferably 200 mPa·s or less (e.g. 150 mPa·s or less), and more preferably 100 mPa·s or less (e.g. 50 mPa·s or less).
[0117] The lower limit of the viscosity of a 4% aqueous solution of the vinyl alcohol resin (A) at 20° C. is not particularly limited, and may be, for example, 1 mPa·s or more, 3 mPa·s or more, or the like.
[0118] In addition, for the viscosity of a 4% aqueous solution of vinyl alcohol resin (A) at 20°C, the above-mentioned upper limit value and lower limit value can be appropriately combined to set an appropriate range (for example, 1 to 300 mPa·s, 1 to 250 mPa·s, etc.) (the same applies to other numerical values), including all combinations of the above-mentioned upper limit value and lower limit value.
[0119] The viscosity of a 4% aqueous solution of the vinyl alcohol resin (A) at 20° C. can be measured, for example, by the method specified in JIS K 6726 (1994).
[0120] The number average molecular weight of the vinyl alcohol resin (A) is not particularly limited, and may be, for example, 10,000 or more, 20,000 or more, 30,000 or more, 40,000 or more, or 50,000 or more.
[0121] The lower limit of the number average molecular weight of the vinyl alcohol-based resin (A) is not particularly limited, and may be, for example, 200,000 or less, 100,000 or less, or the like.
[0122] The number average molecular weight of the vinyl alcohol-based resin (A) can be measured, for example, by GPC (for example, water-based, polyethylene glycol-equivalent) or the like.
[0123] The weight average molecular weight (Mw) of the vinyl alcohol resin (A) is not particularly limited. For example, when the vinyl alcohol resin (A) has a polyoxyethylene group, the weight average molecular weight (Mw) of the vinyl alcohol resin (A) can be, for example, 5,000 to 200,000, preferably 10,000 to 100,000 (e.g. 10,000 to 30,000, 35,000 to 80,000), and more preferably 15,000 to 60,000 (e.g. 20,000 to 40,000).
[0124] The weight average molecular weight of the vinyl alcohol-based resin (A) can be measured, for example, by GPC (for example, water-based, polyethylene glycol-equivalent) or the like.
[0125] In the composition, the water-soluble polymer contains at least a vinyl alcohol resin (B), and the vinyl alcohol resin (B) is at least one selected from a vinyl alcohol resin (B1) having a saponification degree greater than 90 mol% and a 4% aqueous solution viscosity of 300 mPa·s or less at 20°C, and a vinyl alcohol resin (B2) having a saponification degree of 90 mol% or less.
[0126] (Vinyl alcohol resin (B))
[0127] Like the above-mentioned vinyl alcohol resin (A), the vinyl alcohol resin (B) is a saponified product of a vinyl ester polymer.
[0128] As the vinyl ester or other monomer in the vinyl ester polymer, the vinyl ester or other monomer exemplified for the above-mentioned vinyl alcohol resin (A) may be mentioned.
[0129] Typical examples of the vinyl alcohol resin (B) include saponified products of vinyl ester polymers containing at least vinyl ester as a polymerization component.
[0130] The vinyl alcohol resin (B) may have a side chain group having 3 or more carbon atoms (for example, a side chain group derived from diacetone (meth) acrylamide). The side chain group having 3 or more carbon atoms may be the group exemplified for the vinyl alcohol resin (A).
[0131] In addition, the vinyl ester-derived units or units derived from other monomers of the vinyl alcohol resin (B) may be modified within the range that does not hinder the effects of the present invention. For example, the vinyl ester-derived units may be modified by reactions such as acetalization, etherification, acetoacetylation, cationization, polyoxyalkylene modification, etc.
[0132] As described above, the vinyl alcohol resin (B) may contain units other than vinyl alcohol units and vinyl ester units, but the range of these units is preferably less than 1 mol %, and it is preferably composed essentially of vinyl alcohol units and vinyl ester units.
[0133] The vinyl alcohol-based resin (B) can be used alone or in combination of two or more.
[0134] Moreover, as the vinyl alcohol-based resin (B), a commercially available product can be used.
[0135] The method for producing the vinyl alcohol-based resin (B) may be the same as the method for producing the vinyl alcohol-based resin (A) exemplified above.
[0136] (Vinyl alcohol resin (B1))
[0137] The saponification degree of the vinyl alcohol resin (B1) is, for example, greater than 90 mol%, and may be 91 mol% or more, 92 mol% or more, 93 mol% or more, 94 mol% or more, 95 mol% or more, 96 mol% or more, 97 mol% or more, 98 mol% or more, etc.
[0138] Such a vinyl alcohol resin with a high degree of saponification is less likely to undergo saponification reaction in an aqueous solution, so that a polishing composition having excellent storage stability can be easily obtained and pH fluctuation of the polishing composition can be easily reduced.
[0139] The upper limit of the saponification degree of the vinyl alcohol resin (B1) is not particularly limited, and may be, for example, 99.9 mol% or less, 99.5 mol% or less, or 99 mol% or less.
[0140] In addition, for the saponification degree of the vinyl alcohol resin (B1), the above-mentioned upper limit value and lower limit value can be appropriately combined to set an appropriate range (for example, 90 to 99.9 mol%, 91 to 99 mol%, 92 to 99 mol%, etc.) (the same applies to other numerical values), including all combinations of the above-mentioned upper limit value and lower limit value.
[0141] From the perspective of reducing minor defects, etc., the viscosity of a 4% aqueous solution of the vinyl alcohol resin (B1) at 20°C can be relatively low, for example, it can be 300 mPa·s or less (for example, 250 mPa·s or less), preferably 200 mPa·s or less (for example, 180 mPa·s or less), more preferably 150 mPa·s or less (for example, 100 mPa·s or less), and particularly preferably 50 mPa·s or less (for example, 40 mPa·s or less, 30 mPa·s or less, 20 mPa·s or less, 15 mPa·s or less).
[0142] According to the research of the inventors of this application, although when using a vinyl alcohol resin with a high degree of saponification, sometimes the minute defects on the surface of the silicon wafer after grinding are likely to increase, in the present invention, by making the viscosity of the 4% aqueous solution of the vinyl alcohol resin (B1) at 20°C lower, it is easy to reduce the minute defects on the surface of the wafer even when the degree of saponification of the vinyl alcohol resin (B1) is high.
[0143] The lower limit of the viscosity of a 4% aqueous solution of the vinyl alcohol resin (B1) at 20°C is not particularly limited, and may be, for example, 0.5 mPa·s or more, 1 mPa·s or more, 2 mPa·s or more, 5 mPa·s or more, 10 mPa·s or more, 15 mPa·s or more, 20 mPa·s or more, 25 mPa·s or more, 30 mPa·s or more, 40 mPa·s or more, 50 mPa·s or more, etc.
[0144] In addition, for the viscosity of a 4% aqueous solution of the vinyl alcohol resin (B1) at 20°C, the above-mentioned upper limit value and lower limit value can be appropriately combined to set an appropriate range (for example, 0.5 to 300 mPa·s, 1 to 200 mPa·s, 2 to 50 mPa·s, etc.) (the same applies to other numerical values), including all combinations of the above-mentioned upper limit value and lower limit value.
[0145] Furthermore, from the comprehensive perspective of LLS defects, AFM roughness, and haze, the viscosity of a 4% aqueous solution of the vinyl alcohol resin (B1) at 20°C may be a higher viscosity (e.g., 30 mPa·s or more, 40 mPa·s or more, 50 mPa·s or more, etc.) among 300 mPa·s or less. However, from the perspective of suppressing the viscosity increase and gelation during storage, and the operability in an aqueous solution, a lower viscosity (e.g., 40 mPa·s or less, less than 40 mPa·s, 30 mPa·s or less, less than 30 mPa·s, 25 mPa·s or less, less than 25 mPa·s, 20 mPa·s or less, etc.) may be used.
[0146] The average degree of polymerization of the vinyl alcohol resin (B1) is not particularly limited, and may be, for example, 100 to 4000, preferably 200 to 3500, more preferably 300 to 3000, particularly preferably 500 to 2500 (eg 600 to 2300, 1000 to 2000), and the like.
[0147] The weight average molecular weight of the vinyl alcohol resin (B1) is not particularly limited. For example, the weight average molecular weight of the vinyl alcohol resin (B1) having a saponification degree of 95 mol % or more may be, for example, 4,000 to 176,000, preferably 44,000 or more, and from the perspective of improving LLS defects on the surface after polishing, it may be more preferably 44,000 to 88,000, and from the perspective of improving AFM roughness on the surface after polishing, it may be more preferably 155,000 to 176,000.
[0148] (Vinyl alcohol resin (B2))
[0149] From the perspective of reducing minute defects, the saponification degree of the vinyl alcohol resin (B2) is, for example, 90 mol% or less, or 89 mol% or less, 88 mol% or less, 87 mol% or less, 86 mol% or less, 85 mol% or less, etc.
[0150] Such a vinyl alcohol resin with a low degree of saponification tends to suppress an increase in viscosity of the aqueous solution of the vinyl alcohol resin, which is a raw material of the polishing composition, due to storage.
[0151] The lower limit of the saponification degree of the vinyl alcohol resin (B2) is not particularly limited, and may be, for example, 60 mol% or more, 65 mol% or more, 70 mol% or more, 75 mol% or more, 80 mol% or more, or the like.
[0152] In addition, for the saponification degree of the vinyl alcohol resin (B2), the above-mentioned upper limit value and lower limit value can be appropriately combined to set an appropriate range (for example, 60 to 90 mol%, 65 to 89 mol%, 70 to 89 mol%, etc.) (the same applies to other numerical values), including all combinations of the above-mentioned upper limit value and lower limit value.
[0153] The viscosity of a 4% aqueous solution of the vinyl alcohol resin (B2) at 20°C is not particularly limited, and may be, for example, 2000 mPa·s or less, 1000 mPa·s or less, 500 mPa·s or less, 300 mPa·s or less, 100 mPa·s or less, 50 mPa·s or less, etc.
[0154] The viscosity of a 4% aqueous solution of the vinyl alcohol resin (B2) at 20°C may be relatively high.
[0155] According to the research of the inventors of the present application, although a vinyl alcohol resin with a high viscosity of a 4% aqueous solution at 20°C is preferred from the perspective of improving the protection of the wafer surface and reducing damage to the wafer, if a vinyl alcohol resin with a high viscosity of a 4% aqueous solution at 20°C is used for surface grinding of silicon wafers, there is a tendency that micro defects on the wafer surface are easily increased. However, in the present invention, by using a vinyl alcohol resin (B2) with a low degree of saponification, micro defects on the wafer surface are easily reduced even when the 4% aqueous solution viscosity of the vinyl alcohol resin at 20°C is high.
[0156] The lower limit of the viscosity of a 4% aqueous solution of the vinyl alcohol resin (B2) at 20°C is not particularly limited, and may be, for example, 0.5 mPa·s or more, 1 mPa·s or more, 2 mPa·s or more, or the like.
[0157] In addition, for the viscosity of a 4% aqueous solution of the vinyl alcohol resin (B2) at 20°C, the above-mentioned upper limit value and lower limit value can be appropriately combined to set an appropriate range (for example, 0.5 to 2000 mPa·s, 1 to 1000 mPa·s, 2 to 500 mPa·s, etc.) (the same applies to other numerical values), including all combinations of the above-mentioned upper limit value and lower limit value.
[0158] The average degree of polymerization of the vinyl alcohol resin (B2) is not particularly limited, and may be, for example, 100 to 9000, preferably 1800 to 8800, more preferably 3700 to 8500, particularly preferably 4000 to 8000 (eg 4000 to 5000).
[0159] The weight average molecular weight of the vinyl alcohol resin (B2) is not particularly limited. From the perspective of reducing the number of LLS defects on the surface after polishing and reducing the AFM roughness, for example, the weight average molecular weight of the vinyl alcohol resin (B2) having a saponification degree of about 88 mol% (e.g., 85 to 90 mol%) can be preferably 82,000 or more, and can be more preferably 182,000 to 417,000 (e.g., 196,000 to 245,000).
[0160] The weight average molecular weight of the vinyl alcohol resin (B2) having a saponification degree of 75 mol% or more and less than 81 mol% is preferably 30,000 or more, and may be 25,000 or less.
[0161] The weight average molecular weight of the vinyl alcohol-based resin (B2) having a saponification degree of less than 75 mol % may preferably be 10,000 or more.
[0162] The methods for measuring the saponification degree, the viscosity of a 4% aqueous solution at 20° C., the average degree of polymerization and the weight average molecular weight of the vinyl alcohol resin (B) may be the same as those exemplified above for the vinyl alcohol resin (A).
[0163] As the water-soluble polymer, one or two or more selected from vinyl alcohol resins (A) and vinyl alcohol resins (B) can be used.
[0164] The composition may further contain other water-soluble polymers other than the above-mentioned vinyl alcohol resin (A) and vinyl alcohol resin (B).
[0165] Other water-soluble polymers are not particularly limited, and examples thereof include vinyl alcohol resins not included in the scope of the vinyl alcohol resin (A) and the vinyl alcohol resin (B), cellulose derivatives (e.g., methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, ethyl hydroxyethyl cellulose, carboxymethyl cellulose), starch derivatives (e.g., pullulan, cyclodextrin), imine derivatives [e.g., poly(N-acylalkylene imine)], polyvinyl pyrrolidone resins, polyvinyl caprolactam resins, acrylic resins, polyacryloylmorpholine resins, polyoxyalkylenes (e.g., polyoxyethylene), and the like.
[0166] The other water-soluble polymers may be used alone or in combination of two or more.
[0167] (Surfactant)
[0168] The composition may further contain a surfactant.
[0169] By using a surfactant, the dispersion stability of the composition can be improved, and the micro defects and haze of the polished surface can be easily reduced.
[0170] From the viewpoint of dispersibility of the composition and cleaning property of the polishing object, the molecular weight of the surfactant is preferably 1×10 4 the following.
[0171] In addition, the lower limit of the molecular weight of the surfactant can be appropriately selected according to the type of surfactant, for example, it is 200 or more. From the perspective of reducing the effect of microscopic defects and haze on the surface, it is preferably 250 or more, more preferably 300 or more (for example, 500 or more), further preferably 2000 or more, and particularly preferably 5000 or more.
[0172] Specifically, the molecular weight of the surfactant may be, for example, 200 to 10,000, preferably 250 to 10,000, and more preferably 300 to 10,000 (eg, 2,000 to 10,000, 5,000 to 10,000).
[0173] As the molecular weight of the surfactant, the weight average molecular weight (Mw) (water-based, polyethylene glycol-equivalent) determined by GPC or the molecular weight calculated from the chemical formula can be used.
[0174] The surfactant may be a water-soluble polymer having a molecular weight within the above-exemplified range (for example, other water-soluble polymers exemplified above).
[0175] Specific examples of the surfactant include anionic (negative ion) surfactants and nonionic (nonionic) surfactants. Nonionic surfactants are preferred from the viewpoints of low foaming properties and ease of pH adjustment.
[0176] Examples of the nonionic surfactant include copolymers of various olefin oxides (e.g., various olefin oxides such as diblock, triblock, random, and alternating types); 2-6 Copolymers of olefins, preferably oxidized C 2-3 olefin copolymers), olefin oxide polymers (e.g., polyethylene glycol, polypropylene glycol, polybutylene glycol, etc.), polyolefin oxide adducts {e.g., polyoxyethylene adducts [e.g., polyoxyethylene alkyl ethers (e.g., polyoxyethylene propyl ether, polyoxyethylene butyl ether, polyoxyethylene pentyl ether, polyoxyethylene hexyl ether, polyoxyethylene octyl ether, polyoxyethylene 2-ethylhexyl ether, polyoxyethylene nonyl ether, polyoxyethylene decyl ether, polyoxyethylene isodecyl ether, polyoxyethylene tridecyl ether, polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene isostearyl ether, polyoxyethylene oleyl ether), polyoxyethylene phenyl ether, polyoxyethylene alkyl phenyl ether (e.g., polyoxyethylene octyl phenyl ether, polyoxyethylene nonyl phenyl ether, polyoxyethylene dodecyl phenyl ether), polyoxyethylene styrenated phenyl ether, alkylamine poly
[0043] polyoxyethylene ethers (e.g., laurylamine polyoxyethylene ether, stearylamine polyoxyethylene ether, oleylamine polyoxyethylene ether), polyoxyethylene alkylamides (e.g., polyoxyethylene stearamide, polyoxyethylene oleamide), polyoxyethylene fatty acid esters (e.g., polyoxyethylene monolaurate, polyoxyethylene monostearate, polyoxyethylene distearate, polyoxyethylene monooleate, polyoxyethylene dioleate), polyoxyethylene glycerol ether fatty acid esters, polyoxyethylene sorbitan fatty acid esters (e.g., polyoxyethylene monolaurate sorbitan, polyoxyethylene monopalmitate sorbitan, polyoxyethylene monostearate sorbitan, polyoxyethylene monooleate sorbitan, polyoxyethylene trioleate sorbitan), polyoxyethylene tetraoleate sorbitan, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil], etc. 2-6 Olefin adducts, preferably polyoxy C 2-3 Olefin adducts}, acetylene glycol-based surfactants [e.g., ethylene oxide (e.g., ethylene oxide, etc.) adducts of acetylene glycol], and the like.
[0177] Examples of copolymers of a plurality of olefin oxides include copolymers having an ethylene oxide (EO) structure and a propylene oxide (PO) structure (copolymers having an EO-PO structure) {e.g., block copolymers of EO and PO [e.g., diblock copolymers, polyoxyethylene (PEO)-polyoxypropylene (PPO)-PEO type triblock copolymers, PPO-PEO-PPO type triblock copolymers, etc.], random copolymers of EO and PO, etc.} and the like.
[0178] Among these nonionic surfactants, copolymers with an EO-PO structure, polyoxyethylene alkyl ethers, acetylene glycol-based surfactants, etc. are preferred, and block copolymers of EO and PO (especially triblocks of the PEO-PPO-PEO type), random copolymers of EO and PO, polyoxyethylene alkyl ethers (e.g., polyoxyethylene decyl ether), etc. are particularly preferred.
[0179] As the PEO-PPO-PEO type triblock body, a polymer represented by the following general formula (2) can be preferably used.
[0180] HO-(EO) a -(PO) b -(EO) c -H···(2)
[0181] In the general formula (2), EO represents an ethylene oxide unit (-CH2CH2O-), PO represents an propylene oxide unit (-CH2CH(CH3)O-), and a, b and c each represent an integer of 1 or more (typically, 2 or more).
[0182] In the general formula (2), the total of a and c is preferably in the range of 2 to 1,000, more preferably in the range of 5 to 500, and even more preferably in the range of 10 to 200.
[0183] b in the general formula (2) is preferably in the range of 2-200, more preferably in the range of 5-100, and even more preferably in the range of 10-50.
[0184] From the viewpoint of solubility in water and washability, in the block copolymer or random copolymer of EO and PO, the molar ratio of EO to PO constituting the copolymer (EO / PO) is preferably greater than 1, more preferably greater than 2, and further preferably greater than 3 (e.g. greater than 5).
[0185] As the acetylene glycol-based surfactant, for example, SURFYNOL 400 series manufactured by Nissin Chemical Co., Ltd. can be used.
[0186] The surfactant may be used alone or in combination of two or more.
[0187] The HLB value of the surfactant is not particularly limited, and may be, for example, 8 to 20, preferably 10 to 20, and more preferably 15 to 20.
[0188] (Abrasive particles)
[0189] The composition may contain abrasive particles.
[0190] Abrasive particles are not particularly limited, and examples thereof include inorganic particles [e.g., inorganic oxides {e.g., metal oxides (e.g., aluminum oxide, cerium oxide, chromium oxide, titanium dioxide, zirconium oxide, magnesium oxide, manganese dioxide, zinc oxide, red iron oxide), semi-metal oxides (e.g., silicon dioxide)}, metal hydroxides [e.g., rare earth metal hydroxides (e.g., cerium hydroxide), zirconium hydroxide], inorganic nitrides (e.g., silicon nitride, boron nitride), inorganic carbides (e.g., silicon carbide, boron carbide), inorganic carbonates {e.g., metal carbonates such as alkali metal carbonates (e.g., sodium carbonate, potassium carbonate), alkaline earth metal carbonates (e.g., calcium carbonate, barium carbonate)}, diamond, etc.], organic particles [e.g., polymers of unsaturated acids (e.g., poly(meth)acrylic acid), (meth)acrylate polymers {e.g., poly(meth)acrylate alkyl esters (e.g., polymethyl methacrylate)}, polyacrylonitrile, etc.], organic-inorganic composite particles, etc.
[0191] In these abrasive particles, inorganic particles are preferred, inorganic oxides (such as metal oxides, semi-metallic oxides) are more preferred, and silicon dioxide (such as colloidal silica, fumed silica, precipitated silica) is particularly preferred. Therefore, the abrasive particles can contain silicon dioxide at least. When the abrasive particles contain silicon dioxide, the ratio of the silicon dioxide in the abrasive particles can be, for example, more than 50 % by weight (such as more than 60 % by weight), more than 70 % by weight (more than 80 % by weight), more than 90 % by weight (more than 95 % by weight, more than 99 % by weight), etc.
[0192] From the perspective of being less likely to cause scratches on the surface of the polishing object and being able to achieve a surface with lower haze, among silicas, colloidal silica, fumed silica, etc. are preferred. From the perspective of being able to suppress scratches, etc., colloidal silica is more preferred. From the perspective of preventing metal contamination, high-purity colloidal silica is particularly preferred.
[0193] The abrasive particles may be used alone or in combination of two or more.
[0194] The particle form of the abrasive particles is not particularly limited, and may be any of primary particles, secondary particles, and a mixture of primary particles and secondary particles, and is preferably a form containing at least secondary particles.
[0195] The average primary particle size of abrasive particles D P1 There is no particular limitation, but from the viewpoint of polishing speed, etc., it may be, for example, 5 nm or more, preferably 10 nm or more, more preferably 15 nm or more, and even more preferably 20 nm or more.
[0196] In addition, from the perspective of reducing haze, the average primary particle size D of the abrasive particles is P1The diameter may preferably be less than 100 nm, more preferably be 50 nm or less, and even more preferably be 40 nm or less.
[0197] In addition, the average primary particle size D of the abrasive particles P1 The above upper limit value and lower limit value can be appropriately combined to set an appropriate range (for example, 5 nm to 50 nm, 5 nm to 40 nm, etc.) (the same applies to other numerical values).
[0198] The average primary particle size of abrasive particles D P1 For example, the specific surface area S (m 2 / g), through D P1 =2720 / S(nm) is used for calculation.
[0199] The method for measuring the specific surface area is not particularly limited, and the specific surface area can be measured using, for example, a surface area measuring device "Flow Sorb II 2300" manufactured by Micro Meritex.
[0200] Average secondary particle size D of abrasive particles P2 There is no particular limitation, but from the viewpoint of polishing rate, etc., the thickness may be, for example, 10 nm or more, and preferably 20 nm or more.
[0201] In addition, from the perspective of obtaining a higher grinding effect, the average secondary particle size D of the abrasive particles is P2 It may be more preferably 30 nm or more, further preferably 35 nm or more, and particularly preferably 40 nm or more (eg, greater than 40 nm).
[0202] In addition, from the perspective of being easy to exist in the polishing composition as particles of a size suitable for reducing micro defects, the average secondary particle size D of the abrasive particles is P2 For example, it may be less than 100 nm, preferably less than 90 nm, and more preferably less than 80 nm.
[0203] In addition, the average secondary particle size D of the abrasive particles P2 The above upper limit value and lower limit value can be appropriately combined to set an appropriate range (for example, 10 nm to 90 nm, 20 nm to 80 nm, etc.) (the same applies to other numerical values).
[0204] Average secondary particle size D of abrasive particles P2 The measurement can be performed by using an aqueous dispersion of target abrasive particles (not containing a water-soluble polymer) as a measurement sample and by using, for example, a laser diffraction scattering method using model “UPA-UT151” manufactured by Nikkiso Co., Ltd.
[0205] Average secondary particle size D of abrasive particles P2 Can be greater than or equal to the average primary particle size D of the abrasive particles P1 (D P2 / D P1 ≥1), or greater than D P1 (D P2 / D P1 >1).
[0206] From the perspective of grinding effect and surface smoothness after grinding, the D of abrasive particles is P2 / D P1 It is preferably in the range of 1 to 3.
[0207] The shape (outer shape) of the abrasive particles is not particularly limited, and may be spherical or non-spherical {eg, peanut-shaped (ie, peanut shell-shaped), cocoon-shaped, candy-shaped, rugby-shaped}.
[0208] The average value of the major diameter / minor diameter ratio (average aspect ratio) of the primary particles of the abrasive grains is not particularly limited, but is preferably 1.0 or more, more preferably 1.05 or more, and further preferably 1.1 or more from the viewpoint of polishing rate and the like.
[0209] Furthermore, from the viewpoint of reducing scratches, the average aspect ratio of the abrasive grains is preferably 3.0 or less, more preferably 2.0 or less, and further preferably 1.5 or less.
[0210] In addition, the shape (outline) and average aspect ratio of abrasive particles can be grasped by, for example, electron microscope observation. As a specific step, for example, using a scanning electron microscope (SEM), abrasive particles of the shape of independent particles can be identified for a specified number (for example, 200), and the smallest rectangle circumscribed to each particle image is drawn. Then, for the rectangle drawn for each particle image, the value obtained by dividing the length of its long side (the value of the major diameter) by the length of the short side (the value of the minor diameter) is calculated as the major diameter / minor diameter ratio (aspect ratio). By taking the arithmetic average of the aspect ratio of the particles of the above-mentioned specified number, the average aspect ratio can be obtained.
[0211] (pH adjuster)
[0212] The composition may contain a pH adjusting agent.
[0213] As the pH adjuster, a basic compound is preferred from the viewpoints of chemical polishing of the surface of the object to be polished, improvement of the polishing rate, improvement of the dispersion stability of the composition, and the like.
[0214] By using a basic compound, the pH of the composition can be increased.
[0215] Examples of the basic compound include nitrogen-containing organic or inorganic basic compounds [e.g., quaternary ammonium hydroxide or salts thereof (e.g., tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, etc.), ammonia, amines {e.g., methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, monoethanolamine, N-(β-aminoethyl)ethanolamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, guanidine, etc.}, azoles (e.g., anhydrous piperazine, piperazine hexahydrate, 1-(2-aminoethyl)piperazine, N-methylpiperazine, imidazole, triazole, etc.}, etc.], hydroxides of alkali metals or alkaline earth metals (e.g., potassium hydroxide, sodium hydroxide, etc.), carbonates (e.g., ammonium carbonate, potassium carbonate, sodium carbonate, etc.), bicarbonates (e.g., ammonium bicarbonate, potassium bicarbonate, sodium bicarbonate, etc.), and the like.
[0216] Among these alkaline compounds, from the perspective of increasing the polishing rate, etc., preferred are ammonia, alkali metal hydroxides (e.g., potassium hydroxide, sodium hydroxide, etc.), quaternary ammonium hydroxide or its salts (e.g., tetramethylammonium hydroxide, tetraethylammonium hydroxide, etc.), carbonates (e.g., ammonium carbonate, potassium carbonate, sodium carbonate, etc.), bicarbonates (e.g., ammonium bicarbonate, potassium bicarbonate, sodium bicarbonate, etc.), etc.; more preferred are ammonia, potassium hydroxide, sodium hydroxide, tetramethylammonium hydroxide, tetraethylammonium hydroxide, etc.; further preferred are ammonia, tetramethylammonium hydroxide, etc.; and particularly preferred is ammonia.
[0217] The basic compound may be used alone or in combination of two or more.
[0218] (solvent)
[0219] The composition may contain a solvent.
[0220] The solvent is not particularly limited, and examples thereof include water and organic solvents (eg, lower alcohols, lower ketones, etc.).
[0221] The solvent preferably contains at least water.
[0222] The water content in the entire solvent is preferably 90% by volume or more, more preferably 95% by volume or more (eg, 99 to 100% by volume).
[0223] As water, ion-exchanged water (deionized water), pure water, ultrapure water, distilled water, or the like can be preferably used.
[0224] From the viewpoint of avoiding the inhibition of the effects of other components contained in the composition as much as possible, the total content of transition metal ions in water is preferably 100 ppb or less.
[0225] The water may be water having a purity improved by, for example, removing impurity ions using an ion exchange resin, removing foreign matter using a filter, or distilling.
[0226] (Other ingredients)
[0227] In addition to the above-mentioned components (water-soluble polymer, abrasive particles, pH adjuster, surfactant and solvent), the composition may contain other components.
[0228] The other components are not particularly limited, and examples thereof include additives such as chelating agents, organic acids, organic acid salts, inorganic acids, inorganic acid salts, preservatives, and antifungal agents.
[0229] Examples of the chelating agent include aminocarboxylic acid chelating agents and organic phosphonic acid chelating agents.
[0230] Examples of the aminocarboxylic acid chelating agent include ethylenediaminetetraacetic acid, sodium ethylenediaminetetraacetate, nitrilotriacetic acid, sodium nitrilotriacetate, ammonium nitrilotriacetate, hydroxyethylethylenediaminetriacetic acid, sodium hydroxyethylethylenediaminetriacetate, diethylenetriaminepentaacetic acid, sodium diethylenetriaminepentaacetate, triethylenetetraaminehexaacetic acid, and sodium triethylenetetraaminehexaacetate.
[0231] Examples of the organic phosphonic acid chelating agent include 2-aminoethylphosphonic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, aminotri(methylenephosphonic acid), ethylenediaminetetra(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), ethane-1,1-diphosphonic acid, ethane-1,1,2-triphosphonic acid, ethane-1-hydroxy-1,1-diphosphonic acid, ethane-1-hydroxy-1,1,2-triphosphonic acid, ethane-1,2-dicarboxy-1,2-diphosphonic acid, methanehydroxyphosphonic acid, 2-phosphonobutane-1,2-dicarboxylic acid, 1-phosphonobutane-2,3,4-tricarboxylic acid, α-
[0232] Methylphosphonosuccinic acid, etc.
[0233] Among these chelating agents, organic phosphonic acid chelating agents are more preferred, and ethylenediaminetetrakis(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), and the like are particularly preferred.
[0234] Examples of the organic acid include fatty acids (e.g., formic acid, acetic acid, propionic acid, etc.), aromatic carboxylic acids (e.g., benzoic acid, phthalic acid, etc.), citric acid, oxalic acid, tartaric acid, malic acid, maleic acid, fumaric acid, succinic acid, organic sulfonic acids, and organic phosphonic acids.
[0235] Examples of the organic acid salt include alkali metal salts of organic acids (eg, sodium salts, potassium salts, etc.), ammonium salts of organic acids, and the like.
[0236] Examples of the inorganic acid include sulfuric acid, nitric acid, hydrochloric acid, and carbonic acid.
[0237] Examples of the inorganic acid salt include alkali metal salts of inorganic acids (eg, sodium salts, potassium salts, etc.), ammonium salts of inorganic acids, and the like.
[0238] Examples of the preservative and antifungal agent include isothiazolin-based compounds, parabens, and phenoxyethanol.
[0239] The other components may be used alone or in combination of two or more.
[0240] (Form of Composition)
[0241] As described later, the composition may be used as a polishing liquid as it is, or a liquid diluted with a solvent (for example, diluted at a dilution ratio described later) may be used as a polishing liquid.
[0242] That is, the composition may be of low concentration (polishing liquid) or high concentration (polishing concentrate).
[0243] Alternatively, a high concentration composition may be a concentrate of a low concentration composition.
[0244] In the composition, the proportion of the water-soluble polymer (the proportion of the water-soluble polymer to the whole composition) is not particularly limited, and can be, for example, 1 ppm or more on a mass basis, and can preferably be 3 ppm or more from the perspective of reducing haze, and can more preferably be 5 ppm or more (for example, 10 ppm or more).
[0245] Furthermore, in the composition, the proportion of the water-soluble polymer may be preferably 1000 ppm or less, more preferably 500 ppm or less (eg 300 ppm or less) on a mass basis from the viewpoint of polishing rate and the like.
[0246] The above upper limit and lower limit may be appropriately combined to set an appropriate range. Specifically, the proportion of the water-soluble polymer in the composition may be, for example, 1 ppm to 1000 ppm, preferably 3 ppm to 500 ppm, and more preferably 5 ppm to 300 ppm.
[0247] For example, in a high-concentration composition, the proportion of the water-soluble polymer can be appropriately set according to the dilution ratio, etc., and is not particularly limited. On a mass basis, the proportion of the water-soluble polymer can be, for example, 1000 ppm or more, preferably 1500 ppm or more, and more preferably 2000 ppm or more.
[0248] In addition, in a high-concentration composition, the proportion of the water-soluble polymer may be preferably 20,000 ppm or less, and more preferably 10,000 ppm or less, based on mass.
[0249] In addition, the above upper limit and lower limit can be appropriately combined to set an appropriate range. Specifically, in a high-concentration composition, the proportion of the water-soluble polymer can be, for example, 1000 ppm to 20000 ppm, preferably 1500 ppm to 10000 ppm, and more preferably 2000 ppm to 5000 ppm.
[0250] When composition contained abrasive grain, in composition, the ratio of abrasive grain (abrasive grain is relative to the ratio of composition as a whole) is not particularly limited, for example, can be more than 0.01 mass %, can be preferably more than 0.05 mass %, can be more preferably more than 0.1 mass % (for example more than 0.15 mass %, more than 0.2 mass %, more than 0.4 mass %, more than 0.6 mass %, more than 0.8 mass %).By increasing the content of abrasive grain, higher grinding rate can be achieved.
[0251] Furthermore, in the composition, from the viewpoint of achieving a surface with lower haze, the ratio of the abrasive particles may be, for example, 10% by mass or less, preferably 7% by mass or less, and more preferably 5% by mass or less.
[0252] In addition, can suitably combine above-mentioned upper limit and lower limit to set suitable scope, the ratio of abrasive grain comprises all combinations of above-mentioned upper limit and lower limit.Specifically, in composition, the ratio of abrasive grain can for example be 0.01 mass %~10 mass %, can be preferably 0.05 mass %~7 mass %, can be more preferably 0.1 mass %~5 mass %.
[0253] In particular, in the case of a composition containing a vinyl alcohol-based resin (A) having a polyoxyethylene group and silica, the proportion of silica in the composition may be, for example, greater than 0.2 mass % and less than 7 mass % (e.g. greater than 0.2 mass % and less than 5 mass %), preferably greater than 0.3 mass % and less than 6 mass % (e.g. greater than 0.3 mass % and less than 4 mass %), more preferably greater than 0.4 mass % and less than 5 mass % (e.g. greater than 0.5 mass % and less than 4 mass %, greater than 0.6 mass % and less than 3 mass %).
[0254] In the high-concentration composition, the ratio of the abrasive grains can be appropriately set, for example, by the dilution ratio, and is not particularly limited, but is, for example, 0.2 mass % or more, preferably 1 mass % or more, and more preferably 2 mass % or more.
[0255] Furthermore, in the high-concentration composition, the ratio of the abrasive grains is, for example, 50% by mass or less, preferably 20% by mass or less, and more preferably 10% by mass or less.
[0256] In addition, the upper limit and the lower limit mentioned above can be appropriately combined to set an appropriate range. Specifically, in a high-concentration composition, the proportion of the abrasive particles can be, for example, 0.2% to 50% by mass, 1% to 20% by mass, or 2% to 10% by mass.
[0257] When the composition contains a pH adjuster, the ratio of the pH adjuster in the composition (ratio of the pH adjuster to the entire composition) is not particularly limited, and may be, for example, 1 ppm or more, preferably 5 ppm or more, from the perspective of polishing rate, etc.
[0258] Furthermore, in the composition, from the viewpoint of reducing haze, etc., the proportion of the pH adjuster may be, for example, less than 1000 ppm, and may preferably be less than 500 ppm.
[0259] In addition, the above upper limit and lower limit can be appropriately combined to set an appropriate range. Specifically, in the composition, the proportion of the pH adjuster can be, for example, 1 ppm or more and less than 1 ppm.
[0260] 1000ppm, and may be 5ppm or more and less than 500ppm.
[0261] For example, in a high-concentration composition, the ratio of the pH adjuster can be appropriately set according to the dilution ratio, etc., and is not particularly limited, but may be, for example, 20 ppm or more, and may preferably be 100 ppm or more.
[0262] Furthermore, in a high-concentration composition, the proportion of the pH adjuster may be, for example, less than 20,000 ppm, and preferably less than 10,000 ppm.
[0263] The above upper limit and lower limit can be appropriately combined to set an appropriate range. Specifically, in a high-concentration composition, the proportion of the pH adjuster can be, for example, 20 ppm or more and less than 20,000 ppm, and preferably 100 ppm or more and less than 10,000 ppm.
[0264] When the composition contains a surfactant, the proportion of the surfactant in the composition (the proportion of the surfactant relative to the whole composition) is not particularly limited, and from the perspective of the effect of improving minute surface defects and haze, it is, for example, above 0.1 ppm, preferably above 0.5 ppm, more preferably above 1 ppm (for example, above 3 ppm), and further preferably above 5 ppm (for example, above 10 ppm).
[0265] Furthermore, from the viewpoint of polishing rate and the like, the proportion of the surfactant in the composition is, for example, 1000 ppm or less, preferably 500 ppm or less (eg, 300 ppm or less), and more preferably 100 ppm or less.
[0266] The above upper limit and lower limit may be appropriately combined to set an appropriate range. Specifically, the proportion of the surfactant in the composition may be, for example, 0.1 ppm to 1000 ppm, preferably 0.5 ppm to 500 ppm, and more preferably 1 ppm to 100 ppm.
[0267] For example, in a high-concentration composition, the proportion of the surfactant can be appropriately set according to the dilution ratio, etc., and is not particularly limited, and is, for example, 2 ppm or more, preferably 10 ppm or more, more preferably 20 ppm or more, and further preferably 100 ppm or more.
[0268] In addition, in a high-concentration composition, the proportion of the surfactant is, for example, 20,000 ppm or less, preferably 10,000 ppm or less, and more preferably 2,000 ppm or less.
[0269] In addition, the above upper limit and lower limit can be appropriately combined to set an appropriate range. Specifically, in a high-concentration composition, the proportion of the surfactant can be, for example, 2 ppm to 20,000 ppm, preferably 10 ppm to 10,000 ppm, and more preferably 20 ppm to 2,000 ppm.
[0270] The solid content concentration of the composition is not particularly limited, and may be, for example, 0.01% by mass or more, preferably 0.01% by mass to 50% by mass, and more preferably 0.05% by mass to 40% by mass.
[0271] In addition, in a high-concentration composition, the solid content concentration of the composition can be appropriately set according to, for example, the dilution ratio, etc., and is not particularly limited, and is, for example, 1 mass % or more, preferably 2 mass % to 50 mass %, and more preferably 5 mass % to 25 mass %.
[0272] The solid content concentration can be expressed by the mass ratio of the residue in the composition after the composition is dried at 105° C. for 24 hours.
[0273] When the composition contains other components, the proportion of the other components in the composition (the proportion of the other components relative to the entire composition) is not particularly limited, and may be, for example, 0.01 to 30% by mass, preferably 0.01 to 20% by mass, and more preferably 0.01 to 10% by mass.
[0274] In addition, for example, in a high-concentration composition, the ratio of other components can be appropriately set according to the dilution ratio, etc., and is not particularly limited, and may be, for example, 0.2 to 60 mass %, preferably 0.2 to 40 mass %, and more preferably 0.2 to 20 mass %.
[0275] When the composition contains abrasive particles, in the composition, the ratio of water-soluble polymer to abrasive particles is not particularly limited, and the water-soluble polymer:abrasive particles (mass ratio) may be, for example, 10:1 to 1:1000, preferably 5:1 to 1:500, and more preferably 1:1 to 1:100.
[0276] When the composition contains a surfactant, in the composition, the ratio of the water-soluble polymer to the surfactant is not particularly limited, and the water-soluble polymer: surfactant (mass ratio) is, for example, 1:0.01 to 1:200, and may preferably be 1:0.01 to 1:100 (e.g. 1:0.01 to 1:20, more preferably 1:0.05 to 1:15, and particularly preferably 1:0.1 to 1:10).
[0277] From the angle of suppressing abrasive grain cohesion, the Zeta potential of composition is, for example, below-0mV, preferably below-5mV, more preferably below-10mV.In addition, from the angle of grinding speed, the Zeta potential of composition is, for example, above-100mV, preferably above-90mV, more preferably above-80mV.
[0278] The zeta potential of the composition can be measured using, for example, an ultrasonic zeta potential measuring instrument DT-1202 manufactured by Dispersion Technology.
[0279] (Method for preparing composition)
[0280] The method for preparing the composition is not particularly limited, and for example, the components contained in the composition may be mixed. The mixing may be performed at room temperature or while heating.
[0281] The mixing may be performed while stirring, or may be performed using a mixing device (for example, a paddle stirrer, an ultrasonic disperser, a homomixer, etc.).
[0282] The order of mixing the components in the composition is not particularly limited, and for example, all the components may be mixed at once or in an appropriately set order.
[0283] During the preparation process of the composition, the composition may be filtered.
[0284] Regarding filtration, each component contained in the composition may be filtered, or a mixed solution of the components may be filtered.
[0285] The filtering method is not particularly limited, and for example, filtering can be performed using a filter.
[0286] In addition, the filtration may be a circulation filtration or the like.
[0287] (grinding)
[0288] The polished object can be produced by polishing the surface of the polishing object using the composition.
[0289] The surface to be polished may be either both surfaces or one surface of the object to be polished.
[0290] Furthermore, when polishing both surfaces of the object to be polished, both surfaces may be polished at the same time, or each single surface may be polished one by one.
[0291] Hereinafter, a preferred embodiment of a method for polishing an object to be polished using a composition (a method for producing a polished object) will be described.
[0292] Examples of the material of the object to be polished include metals or semi-metals such as silicon, aluminum, nickel, tungsten, copper, tantalum, titanium, and stainless steel, or alloys of these metals or semi-metals; glassy substances such as quartz glass, aluminosilicate glass, and glassy carbon; ceramic materials such as aluminum oxide, silicon dioxide, sapphire, silicon nitride, tantalum nitride, and titanium carbide; compound semiconductor substrate materials such as silicon carbide, gallium nitride, and gallium arsenide; and resin materials such as polyimide resin.
[0293] Among these polishing objects, silicon (for example, a single crystal silicon substrate, etc.) is preferably contained.
[0294] The object to be polished can be made of a variety of materials.
[0295] A coating may be formed on the polishing object. In the present invention, it is preferred to polish the substrate itself [not the barrier layer (e.g., a barrier layer of tantalum or the like for protecting the insulating layer) formed on the substrate but the substrate itself]. In addition, examples of the coating include polysilicon films, nitride films, oxide films, etc. In addition, the thickness of the coating may be, for example, greater than 100 nm.
[0296] Furthermore, the polishing target surface may be a surface of the substrate that is partially oxidized (for example, a surface having a natural oxide film with a thickness of 100 nm or less).
[0297] The shape of the object to be polished is not particularly limited, but is preferably a shape having a flat surface such as a plate or a polyhedron.
[0298] The area of the object to be polished is not particularly limited, and may be, for example, about 7,000 to about 200,000 mm. 2 (For example, about 7850 to about 196250 mm 2 ), preferably about 17000 to about 160000 mm 2 (For example, about 17663 to about 158963 mm 2 )wait.
[0299] As the polishing liquid used for polishing, the composition may be used directly, or a liquid obtained by diluting the composition with a solvent may be used.
[0300] As diluting solvent, the solvent of above-mentioned illustration etc. can be used, preferably the solvent (aqueous solvent) containing water at least.In addition, diluting solvent can be identical with the solvent contained in composition (the kind of solvent or the mixing ratio of each component when being mixed solvent is identical), also can be different.
[0301] The dilution ratio may be, for example, about 2 to 100 times (eg, about 5 to 50 times, 20 to 50 times) in terms of volume conversion, preferably 10 to 30 times, and more preferably 15 to 25 times.
[0302] Furthermore, the pH of the polishing liquid can be adjusted by using the pH adjuster exemplified above.
[0303] The pH of the polishing liquid can be appropriately adjusted according to the saponification degree of the vinyl alcohol resin or the type of abrasive particles, etc., without particular limitation, and can be, for example, 8.0 to 12.0 (e.g., 9.0 to 11.0), or 5.0 to 9.0 (e.g., 6.0 to 8.0). The above pH can be particularly preferably applied to the polishing liquid used when polishing silicon wafers (e.g., the polishing liquid for final polishing, etc.).
[0304] The polishing liquid is supplied to the polishing object, and polishing can be performed by a conventional method.
[0305] The composition can be particularly preferably used for polishing a semiconductor substrate (particularly a silicon wafer).
[0306] The polishing process using the composition is not particularly limited, and is particularly suitable for, for example, final polishing of a silicon wafer or a higher-order polishing process.
[0307] In addition, final polishing generally refers to the last polishing step in the manufacturing process of the target product (i.e., a step after which no further polishing is performed). For example, it can be effectively applied to the polishing of silicon wafers whose surface roughness is adjusted to 0.01 nm to 100 nm by a high-level process (as a typical example, the final polishing or the polishing before that), and is particularly preferably applied to the final polishing.
[0308] For example, when performing the final polishing of a silicon wafer, the silicon wafer that has undergone the polishing process and the primary and secondary polishing processes can be placed on a conventional polishing device, and the polishing pad of the polishing device can be used to supply the polishing liquid to the surface (polishing target surface) of the silicon wafer. For example, the polishing liquid can be continuously supplied, and the polishing pad can be pressed against the surface of the silicon wafer at the same time, so that the two are moved relative to each other (for example, rotationally moved).
[0309] (Cleaning)
[0310] The ground material obtained in the above manner may be washed.
[0311] Cleaning can be performed using, for example, a cleaning liquid.
[0312] The cleaning liquid is not particularly limited, and when the semiconductor substrate is polished, for example, a conventional SC-1 cleaning liquid (a mixture of ammonium hydroxide (NH4OH), hydrogen peroxide (H2O2), and water (H2O)) in the semiconductor field can be used.
[0313] The temperature of the cleaning liquid can be set to, for example, about room temperature to about 90°C.
[0314] (Grinding material)
[0315] The present invention also includes a polishing material having the following polishing surface.
[0316] The grinding surface of the grinding material can preferably meet the requirement of having an area of about 70650 mm for every 300 mm of diameter (ie, the area of a circle with a diameter of 300 mm: about 70650 mm 2 ), the number of LLS defects above 26 nm is 700 or less, more preferably 300 or less, and further preferably 100 or less.
[0317] The polishing material of the present invention can be the polishing material of the polishing object exemplified above (such as a single crystal silicon substrate, etc.), but is preferably not a polishing material of a single crystal silicon substrate doped with nitrogen, and is preferably not a polishing material of a single crystal silicon substrate having a mixture of Nv and Ni regions.
[0318] The number of LLS defects of 26 nm or more can be measured, for example, by the method described in Examples below.
[0319] In addition, the grinding surface of the grinding object can preferably meet the requirements of every 300 mm diameter (that is, the area of a circle with a diameter of 300 mm: about 70650 mm). 2 ) in which the number of LLS defects above 19 nm is 850 or less, more preferably 550 or less, and further preferably 250 or less.
[0320] The number of LLS defects of 19 nm or more can be measured, for example, by the method described in Examples below.
[0321] Although the number of LLS defects is calculated as the number of defects per 300 mm diameter, the size of the object to be polished is not limited to a circle with a diameter of 300 mm.
[0322] The present invention focuses on surface defects of a smaller size that cannot be measured by the wafer defect inspection device with the product name "SP1" or "SP2" manufactured by KLA-Tencor Corporation, and can reduce the number of such small surface defects. In addition, since the size of the defects measured by using SP1 or SP2 is larger than the size of the defects that can be reduced by the present invention, they cannot be compared with the present invention.
[0323] The haze of the polished surface of the polished material is, for example, less than 0.3 ppm (for example, less than 0.3 ppm), preferably less than 0.25 ppm (for example, less than 0.25 ppm, 0.01 ppm to 0.25 ppm), more preferably less than 0.20 ppm (for example, less than 0.20 ppm, 0.01 ppm to 0.20 ppm), particularly preferably less than 0.15 ppm (for example, less than 0.15 ppm, 0.01 ppm to 0.15 ppm), and most preferably less than 0.10 ppm (for example, less than 0.10 ppm, 0.01 ppm to 0.10 ppm).
[0324] In addition, the haze can be measured by the method described in Examples below.
[0325] The polished surface of the polished object can preferably meet the requirements of 30×30 μm using an atomic force microscope. 2 The root mean square height (Sq) measured in the field of view is less than 0.030 nm, and may be further preferably less than 0.028 nm.
[0326] The lower limit of the root mean square height (Sq) is not particularly limited, and may be, for example, 0.005 nm or more, 0.01 nm or more, or the like.
[0327] The root mean square height (Sq) can be measured by the method described in Examples below.
[0328] The polished object having the above-mentioned polished surface can be obtained, for example, by polishing and washing an object to be polished using a polishing composition containing a water-soluble polymer.
[0329] Examples of the water-soluble polymer include a water-soluble polymer having a long side chain [for example, a water-soluble polymer having a side chain group having 3 or more carbon atoms (for example, a side chain group having 3 or more carbon atoms exemplified for the vinyl alcohol resin (A))], a water-soluble polymer having a low viscosity (for example, a water-soluble polymer having a viscosity of 300 mPa·s or less in a 4% aqueous solution at 20° C.), and the like.
[0330] As the water-soluble polymer, for example, a vinyl alcohol resin can be preferably used. By using the vinyl alcohol resin (A) or the vinyl alcohol resin (B), a polished product having the above-mentioned polished surface can be easily and efficiently obtained.
[0331] Furthermore, the water-soluble polymer may have few properties (for example, aggregation, separation, thickening, gelation, etc.) that are considered to affect the generation of micro defects.
[0332] In addition, the water-soluble polymer may be a water-soluble polymer with a small amount of coarse components, a water-soluble polymer with a small amount of metal impurities (for example, Ni, Cu, etc.), or the like.
[0333] The water-soluble polymer can be obtained by, for example, filtration or ion exchange treatment.
[0334] Example
[0335] Hereinafter, the present invention will be specifically described with reference to Examples, but the present invention is not limited to these Examples.
[0336] In the following examples, "parts" and "%" mean "parts by mass" and "mass %" unless otherwise specified.
[0337] The physical property evaluations in the examples were performed by the following methods.
[0338] (1) Residual amount of diacetone acrylamide:
[0339] CDCl3 was used as solvent and measured 1 H-NMR, calculated from the integrated values of the assigned peaks.
[0340] (2) Vinyl acetate residue:
[0341] CDCl3 was used as solvent and measured 1 H-NMR, calculated from the integrated values of the assigned peaks.
[0342] (3) Residual amount of hexadecyl vinyl ether:
[0343] CDCl3 was used as solvent and measured 1 H-NMR, calculated from the integrated values of the assigned peaks.
[0344] (4) Polymerization yield:
[0345] Each polymerization paste was dried thoroughly and the solid content concentration was measured. The product of the yield coefficient obtained by the following calculation formula and the solid content concentration was taken as the polymerization yield. In addition, when diacetone acrylamide or hexadecyl vinyl ether remained in the solid content, CDCl3 was used as a solvent and the solid content concentration was measured. 1 In H-NMR, the residual amount is calculated from the integrated value of the assigned peak, and the difference obtained by subtracting the residual amount from the solid content concentration is used.
[0346] Yield coefficient = total amount added / total amount of monomer added
[0347] In addition, the total amount added in the above calculation formula refers to the total amount of components added to the reaction system for polymerization, such as monomers, solvents, and initiators.
[0348] (5) 4% aqueous solution viscosity: determined in accordance with JIS K 6726 (1994).
[0349] (6) Saponification degree: determined in accordance with JIS K 6726 (1994).
[0350] (7) Diacetone acrylamide unit content: DMSO-d6 was used as solvent and 1 H-NMR measurement was calculated from the integrated value of the assigned peak.
[0351] (8) Hexadecyl vinyl ether unit content: DMSO-d6 was used as a solvent and 1 H-NMR measurement was calculated from the integrated value of the assigned peak.
[0352] (Water-soluble polymer)
[0353] (Synthesis example 1)
[0354] In a flask equipped with a stirrer, a thermometer, a dropping funnel, and a reflux condenser, 2000 parts of vinyl acetate, 604 parts of methanol, and 8.2 parts of diacetone acrylamide (DAAM) were added, and after nitrogen substitution inside the system, the internal temperature was raised to 60°C. After the temperature was raised, a solution of 1.2 parts of 2,2-azobisisobutyronitrile dissolved in 100 parts of methanol was added to initiate polymerization. While nitrogen was continuously circulated in the flask, a solution of 127.8 parts of diacetone acrylamide dissolved in 80 parts of methanol was dripped at a constant rate immediately after the polymerization was initiated. At the end of the polymerization, m-dinitrobenzene was added as a polymerization inhibitor to stop the polymerization. The yield at the end of the polymerization was 73.8%.
[0355] While adding methanol vapor to the obtained reaction mixture, the remaining vinyl acetate was distilled off to obtain a 50% methanol solution of diacetone acrylamide-vinyl acetate copolymer. To 500 parts of the solution, 70 parts of methanol, 2 parts of ion exchange water and 15 parts of a 4% methanol solution of sodium hydroxide were added, and the mixture was fully mixed and saponified at 45°C. The obtained gel-like substance was crushed, washed with methanol and then dried to obtain a PVA-based resin (DA-PVA1). The viscosity of the 4% aqueous solution of the obtained DA-PVA1 was 20.5 mPa·s, and the degree of saponification was 98.6 mol%. In addition, the diacetone unit content in DA-PVA1 was 4.6 mol%.
[0356] (Synthesis Examples 2 to 7)
[0357] DA-PVA2 to DA-PVA7 described in Table 1 or Table 2 were obtained in the same manner as in Synthesis Example 1 except that the charging blending ratio or saponification conditions during polymerization were changed so as to obtain a PVA-based resin having a modification degree or saponification degree described in Table 1 or Table 2.
[0358] (Synthesis Example 8)
[0359] 2000 parts of vinyl acetate, 781.7 parts of methanol, and 12.5 parts of hexadecyl vinyl ether (HDVE) were added to a flask equipped with a stirrer, a thermometer, a dropping funnel, and a reflux condenser. After the system was purged with nitrogen, the internal temperature was raised to 60°C. After the temperature was raised, a solution of 1.6 parts of 2,2-azobisisobutyronitrile dissolved in 100 parts of methanol was added to initiate polymerization. Nitrogen was continuously circulated in the flask, and at the same time, a solution of 141.1 parts of diacetone acrylamide dissolved in 80 parts of methanol was dripped at a constant rate immediately after the polymerization was initiated. At the end of the polymerization, m-dinitrobenzene was added as a polymerization inhibitor to stop the polymerization. The polymerization yield was 87.7%.
[0360] While adding methanol vapor to the obtained reaction mixture, the remaining vinyl acetate and hexadecyl vinyl ether were distilled off to obtain a 53% methanol solution of diacetone acrylamide-hexadecyl vinyl ether-vinyl acetate copolymer. To 500 parts of the solution, 70 parts of methanol, 2 parts of ion exchange water and 15 parts of a 4% methanol solution of sodium hydroxide were added, and the mixture was fully mixed and saponified at 45°C. The obtained gel-like substance was crushed, fully washed with methanol, and then dried to obtain the PVA-based resin (DAHD-PVA) described in Table 1.
[0361] (Synthesis Examples 9 to 18)
[0362] Based on the method described in Manufacturing Example 1 of Japanese Patent Gazette No. 2013-153149, the polymerization conditions (addition blending ratio, temperature, pressure, polymerization time, etc. during polymerization) or saponification conditions (temperature, time, etc. during saponification) were changed in a manner to obtain PVA with a viscosity and saponification degree of 4% described in Table 1 or Table 4 (for PVA-3, the viscosity of the 4% aqueous solution is 226.1 mPa·s, and the saponification degree is 99.3 mol%), thereby obtaining PVA-1 to PVA-2 and PVA-6, PVA-3 described in Table 1 and PVA-8 to PVA-13 described in Table 4.
[0363] (Example 1)
[0364] A colloidal silica dispersion having a pH adjusted to 10.0 was prepared by adding ammonia water containing ammonia (NH3) as a basic compound at a concentration of 29% to an aqueous solution containing colloidal silica having an average primary particle size of 35 nm as abrasive particles at a concentration of 1%. DA-PVA1 was added to the colloidal silica dispersion in an amount of 100 ppm in the total amount of the liquid to obtain a composition (polishing liquid). The content of silica in the composition was 1%.
[0365] (Examples 2 to 7)
[0366] In the example using the water-soluble polymer described in Table 1 and recorded as EOPO, a composition was obtained in the same manner as in Example 1, except that a copolymer having an EO-PO structure (manufactured by Wako Pure Chemical Industries, Ltd., polyoxyethylene polyoxypropylene glycol (160E.O.) (30P.O.)) was added to the colloidal silica dispersion in an amount of 10 ppm based on the total liquid.
[0367] (Examples 8 to 9)
[0368] In the example using the water-soluble polymer described in Table 1 and recorded as EOPO, a composition was obtained in the same manner as in Example 1, except that a copolymer having an EO-PO structure (manufactured by Wako Pure Chemical Industries, Ltd., polyoxyethylene polyoxypropylene glycol (160E.O.) (30P.O.)) was added to the colloidal silica dispersion in an amount of 10 ppm based on the total liquid.
[0369] (Examples 18 to 19)
[0370] In the example using the water-soluble polymer described in Table 1 and recorded as EOPO, a composition was obtained in the same manner as in Example 1, except that a copolymer having an EO-PO structure (manufactured by Wako Pure Chemical Industries, Ltd., polyoxyethylene polyoxypropylene glycol (160E.O.) (30P.O.)) was added to the colloidal silica dispersion in an amount of 10 ppm based on the total liquid.
[0371] (Example 20)
[0372] A composition was obtained in the same manner as in Example 1 except that PVA-7 obtained by mixing PVA-3 and PVA-5 at a ratio of PVA-3:PVA-5 (mass ratio) = 82:18 was used.
[0373] (Comparative Example 1)
[0374] A composition was obtained in the same manner as in Example 1 except that hydroxyethyl cellulose (manufactured by Daicel FineChem Ltd., hydroxyethyl cellulose SE400) was used as the water-soluble polymer.
[0375] (Comparative Example 2)
[0376] A composition was obtained in the same manner as in Example 1, except that hydroxyethyl cellulose (manufactured by Daicel FineChem Ltd., hydroxyethyl cellulose SE400) was used as a water-soluble polymer and a copolymer having an EO-PO structure (manufactured by Wako Pure Chemical Industries, Ltd., polyoxyethylene polyoxypropylene glycol (160E.O.) (30P.O.)) was added to the colloidal silica dispersion in an amount of 10 ppm based on the total liquid.
[0377] (Comparative Example 3)
[0378] A composition was obtained in the same manner as in Example 1 except that polyvinyl pyrrolidone (manufactured by Wako Pure Chemical Industries, Ltd., polyvinyl pyrrolidone K90) was used as the water-soluble polymer.
[0379] (Reference Examples 1 to 3)
[0380] In the example using the water-soluble polymer described in Table 1 and recorded as EOPO, a composition was obtained in the same manner as in Example 1, except that a copolymer having an EO-PO structure (manufactured by Wako Pure Chemical Industries, Ltd., polyoxyethylene polyoxypropylene glycol (160E.O.) (30P.O.)) was added to the colloidal silica dispersion in an amount of 10 ppm based on the total liquid.
[0381] In addition, as each water-soluble polymer described in Table 1, the following substances were used.
[0382] PVA-4: Made by JAPAN VAM&POVAL Co., Ltd., JMR-800HH
[0383] PVA-5: Made by JAPAN VAM&POVAL Co., Ltd., JMR-500HH
[0384] <Silicon wafer polishing>
[0385] The surface of a silicon wafer was polished under the following conditions using the polishing liquid of each example.
[0386] As the silicon wafer, a single crystal silicon wafer having a diameter of 300 mm, a P-type conductivity, a crystal orientation of <100>, and a resistivity of 0.1 Ω·cm or more and less than 100 Ω·cm is used.
[0387] The polishing evaluation was performed using a blade grinder model "PNX-332B" manufactured by Okamoto Machine Tool Works, Ltd., in two stages: preliminary polishing for unifying the state of the front surface and final polishing using the above composition.
[0388] [Pre-grinding conditions]
[0389] Abrasive cloth: non-woven fabric
[0390] Polishing liquid: Colloidal silica solution adjusted to pH 11 with KOH
[0391] Grinding pressure: 30kPa
[0392] Grinding disc speed: 50rpm
[0393] Grinding head speed: 50rpm
[0394] Grinding time: 3 minutes
[0395] [Fine grinding conditions]
[0396] Abrasive cloth: Suede
[0397] Grinding pressure: 15kPa
[0398] Grinding disc speed: 30rpm
[0399] Grinding head speed: 30rpm
[0400] Grinding time: 3 minutes
[0401] <Cleaning>
[0402] The polished silicon wafer was cleaned using a mixture of NH4OH, H2O2 and ultrapure water (SC1) (the volume ratio of NH4OH:H2O2:ultrapure water was 1:3:30).
[0403] <Minor defect inspection>
[0404] (LLS defect count above 26nm)
[0405] The surface of the cleaned silicon wafer was inspected for the number of LLS defects of 26 nm or more per 300 mm diameter using a wafer defect inspection device called "SP3" manufactured by KLA-Tencor Corporation. The results were evaluated on the following four levels. In addition, the number of LLS defects was measured by removing the outer 3 mm of the surface of the silicon wafer with a diameter of 300 mm.
[0406] A: The number of tests is less than 100
[0407] B: The number of tests is greater than 100 and less than 300
[0408] C: The number of tests is greater than 300 and less than 700
[0409] D: The number of tests is greater than 700
[0410] (LLS defect count above 19nm)
[0411] The surface of the cleaned silicon wafer was inspected for the number of LLS defects of 19 nm or more per 300 mm diameter using a wafer defect inspection device called "SP5" manufactured by KLA-Tencor Corporation. The results were evaluated on the following four levels. In addition, the number of LLS defects was measured by removing the outer 3 mm of the surface of the silicon wafer with a diameter of 300 mm.
[0412] A: The number of tests is less than 250
[0413] B: The number of tests is greater than 250 and less than 550
[0414] C: The number of tests is greater than 550 and less than 850
[0415] D: The number of tests is greater than 850
[0416] <Haze measurement>
[0417] The haze (ppm) of the cleaned silicon wafer surface was measured in DWO mode using a wafer inspection apparatus with a product name of "SP3" manufactured by KLA-Tencor Corporation. The measurement results were evaluated in the following four levels.
[0418] A: less than 0.10ppm
[0419] B: 0.10 ppm or more and less than 0.20 ppm
[0420] C: 0.20 ppm or more and less than 0.30 ppm
[0421] D: 0.30ppm or more
[0422] <AFM Roughness Measurement>
[0423] The cleaned silicon wafer surface was evaluated using an atomic force microscope (AFM). Three points with coordinates of (0 mm, 0 mm), (75 mm, 0 mm), and (145 mm, 0 mm) were observed, with the field of view set to 30 × 30 μm. 2 After the roughness parameters were slope-corrected in the X and Y directions, the root mean square height (Sq) was calculated, and the average of the three points was used as the evaluation index. The results are shown in Table 1 in the following three levels.
[0424] A: less than 0.028nm
[0425] B: 0.028 nm or more and less than 0.030 nm
[0426] C: 0.030nm or more
[0427] Table 1 shows the evaluation results of Examples 1 to 9, Examples 18 to 20, Comparative Examples 1 to 3, and Reference Examples 1 to 3.
[0428] [Table 1]
[0429]
[0430] As shown in Table 1, in Examples 1 to 9 and 18 to 20, the number of LLS defects of 26 nm or more was reduced.
[0431] In addition, in Examples 1 to 9 and 18 to 20, the haze was small.
[0432] Furthermore, in Examples 1 to 9 and 18 to 20, the AFM roughness was small.
[0433] (Examples 10 to 17)
[0434] For the example using the water-soluble polymer described in Table 2 and recorded as EOPO, a composition was obtained in the same manner as in Example 1 except that a copolymer having an EO-PO structure (manufactured by Wako Pure Chemical Industries, Ltd., polyoxyethylene polyoxypropylene glycol (160E.O.) (30P.O.)) was added to the colloidal silica dispersion in an amount of 10 ppm based on the total liquid.
[0435] Table 2 shows the evaluation results.
[0436] In addition, Table 3 shows the evaluation results of the number of LLS defects of 19 nm or more for Examples 1 to 5.
[0437] [Table 2]
[0438]
[0439] [Table 3]
[0440]
[0441] As shown in Tables 2 and 3, in Examples 1 to 5 and 10 to 17, the number of LLS defects of 19 nm or more was reduced.
[0442] Furthermore, as shown in Table 2, in Examples 10 to 17, the haze was small.
[0443] Furthermore, in Examples 10 to 17, the AFM roughness was small.
[0444] (Examples 21 to 30)
[0445] A composition was obtained in the same manner as in Example 1 except that a colloidal silica dispersion at pH 7.2 containing colloidal silica having an average primary particle size of 35 nm as abrasive particles at a concentration of 1% and a water-soluble polymer listed in Table 4 was used.
[0446] In addition, in the examples described as EOPO, a copolymer having an EO-PO structure was added in the same manner as above.
[0447] (Comparative Example 4)
[0448] A composition was obtained in the same manner as in Example 21 except that hydroxyethyl cellulose (manufactured by Daicel FineChem Ltd., hydroxyethyl cellulose SE400) was used as the water-soluble polymer.
[0449] (Comparative Example 5)
[0450] A composition was obtained in the same manner as in Example 21, except that hydroxyethyl cellulose (manufactured by Daicel FineChem Ltd., hydroxyethyl cellulose SE400) was used as a water-soluble polymer and a copolymer having an EO-PO structure (manufactured by Wako Pure Chemical Industries, Ltd., polyoxyethylene polyoxypropylene glycol (160E.O.) (30P.O.)) was added to the colloidal silica dispersion in an amount of 10 ppm based on the total liquid.
[0451] Table 4 shows the evaluation results of Examples 21 to 30 and Comparative Examples 4 and 5.
[0452] [Table 4]
[0453]
[0454] As shown in Table 4, in Examples 21 to 30, the number of LLS defects of 26 nm or more was reduced.
[0455] Furthermore, in Examples 21 to 30, the haze was small.
[0456] Furthermore, in Examples 21 to 30, the AFM roughness was small.
[0457] Industrial Applicability
[0458] The composition of the present invention can achieve reduction of LLS defects of the polishing object, etc., and thus can efficiently process a substrate having a protective film formed on the surface, and is extremely useful industrially.
Claims
1. A polishing composition comprising a water-soluble polymer, wherein: The water-soluble polymer contains at least a vinyl alcohol resin (A) having a side chain group having 3 or more carbon atoms and a saponification degree of 95 mol % or more, The side chain groups include those selected from C 3-30 at least one of a group derived from an alkyl vinyl ether, a group derived from diacetone (meth) acrylamide, and an epoxy ring-opened product of a group derived from a vinyl monomer containing an acetoacetyl group and an epoxy group, The proportion of the water-soluble polymer in the composition is 1000 ppm or less.
2. A polishing composition comprising a water-soluble polymer, wherein: The water-soluble polymer contains at least a vinyl alcohol resin (B1) having a saponification degree of 95 mol % or more and a 4% aqueous solution viscosity of 300 mPa·s or less at 20° C. The vinyl alcohol resin (B1) is basically composed of vinyl alcohol units and vinyl ester units.
3. The polishing composition according to claim 1, wherein The side chain group includes at least one selected from a group derived from diacetone (meth)acrylamide and a polyoxyethylene group.
4. The polishing composition according to claim 1, wherein The side chain groups of the vinyl alcohol resin (A) include 3-30 At least one of a group derived from an alkyl vinyl ether and a group derived from diacetone (meth) acrylamide, wherein the degree of saponification of the vinyl alcohol-based resin (A) is 98 mol% or more.
5. The polishing composition according to claim 1 or 3, wherein The side chain groups contain at least a group derived from diacetone (meth)acrylamide.
6. The polishing composition according to claim 1, wherein The side chain group having 3 or more carbon atoms of the vinyl alcohol resin (A) includes a group derived from an alkyl vinyl ether having 4 or more carbon atoms, and the vinyl alcohol resin (A) has a 4% aqueous solution viscosity of 100 mPa·s or more at 20° C. and a number average molecular weight of 10,000 or more.
7. The polishing composition according to claim 1 or 3, wherein The ratio of the side chain group is 0.05 mol% or more in terms of the polymerized component (monomer).
8. The polishing composition according to claim 1 or 3, wherein The vinyl alcohol resin (A) has a saponification degree of 99.9 mol% or less, and a 4% aqueous solution viscosity at 20°C of 1 to 300 mPa·s. 9 . The polishing composition according to claim 1 , further comprising abrasive grains. 10 . The polishing composition according to claim 1 , further comprising a pH adjuster.
11. The polishing composition according to any one of claims 1 to 3, further comprising abrasive grains and a pH adjuster, wherein: The abrasive grains contain silicon dioxide, and the pH adjuster contains a basic compound.
12. The polishing composition according to claim 2, wherein The abrasive grains contain silicon dioxide. 13 . The polishing composition according to claim 1 , further comprising a surfactant.
14. The polishing composition according to any one of claims 1 to 3, further comprising a surfactant, wherein: The surfactant includes at least one selected from a copolymer having an oxyethylene-oxypropylene structure and a polyoxyethylene alkyl ether.
15. The polishing composition according to any one of claims 1 to 3, further comprising a surfactant, wherein: In terms of mass ratio, the ratio of water-soluble polymer to surfactant is 1:0.01 to 1:
200. 16 . The polishing composition according to claim 1 , further comprising a solvent containing at least water, wherein the concentration of the water-soluble polymer is 1 ppm or more. 17 . The polishing composition according to claim 1 , further comprising a solvent containing at least water, wherein the polishing composition has a solid content concentration of 0.01% by mass or more.
18. A method for producing a polished object, comprising the step of polishing the surface of an object to be polished using a polishing composition containing a water-soluble polymer, wherein: Water-soluble polymers are: (1) a water-soluble polymer containing at least a vinyl alcohol resin (A) having a side chain group having 3 or more carbon atoms and a saponification degree of 95 mol % or more, wherein the side chain group comprises a vinyl alcohol resin selected from 3-30 At least one of a group of an alkyl vinyl ether, a group derived from diacetone (meth) acrylamide, and an epoxy ring-opened product of a group derived from a vinyl monomer containing an acetoacetyl group and an epoxy group; or (2) A water-soluble polymer containing at least a vinyl alcohol resin (B1) having a saponification degree of 95 mol % or more and a 4% aqueous solution viscosity at 20° C. of 300 mPa·s or less.
19. The method for producing a polished article according to claim 18, comprising a dilution step of diluting the polishing composition with a solvent containing at least water, and in the polishing step, polishing is performed using the diluted solution obtained in the dilution step.
20. The method for producing an abrasive according to claim 18 or 19, wherein the abrasive has a surface satisfying the following condition (A): (A) The number of LLS defects of 26 nm or more is 700 or less per 300 mm diameter.
